Determinants of the Use of Electronic Money (e-money) among Muslim Professionals in Medan City - Opi Chanty Mahendra; Sugianto Sugianto; Yenni Samri Juliati Nst (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article analyzes the factors that influence the behavior of new products with a case study of electronic money which is considered a new product category of payment tools in Indonesia. This study integrates the Theory of Acceptance Model (TAM) and Theory of Planned Behavior (TPB). This study is descriptive and exploratory quantitative research. Data was collected on Muslim professionals in Medan city. Structured Equation Modeling (SEM) is used to test the hypothesis in terms of evaluating the effect of the hypothesis research. The results found that the behavior of electronic money is influenced by attitude, perceived behavior control, and subjective norm.